2008
DOI: 10.1063/1.3013313
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of temperature after hypervelocity collision of microparticles in the range from 10 to 40 km/s

Abstract: The temperature recorded immediately after hypervelocity collision of microparticles comprising iron and nickel with a silver-coated piezoelectric plate was analyzed using photomultipliers of different spectral response characteristics. The conversion rate between the velocity and temperature is estimated to be ~900 K/km/s in the velocity range of 10-40 km/s. This rate is greater than that reported earlier

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
1
7
2
Order By: Relevance
“…They found, however, that the expansion speed of the emitted cloud is only proportional to the square root of the impactor speed, not directly. More recently, Miyachi et al [2008] have found that the temperature of the emitted cloud is proportional to the impactor velocity, agreeing with the Goller and Grun square root dependence. This weaker dependence on the impactor speed seems to be a result of adiabatic expansion during the collisional phase.…”
Section: Impact Physics-laboratory Measurements and Simulationssupporting
confidence: 78%
“…They found, however, that the expansion speed of the emitted cloud is only proportional to the square root of the impactor speed, not directly. More recently, Miyachi et al [2008] have found that the temperature of the emitted cloud is proportional to the impactor velocity, agreeing with the Goller and Grun square root dependence. This weaker dependence on the impactor speed seems to be a result of adiabatic expansion during the collisional phase.…”
Section: Impact Physics-laboratory Measurements and Simulationssupporting
confidence: 78%
“…Laboratory measurements and theory yield various and conflicting results, including calculated temperatures of about 1 eV at impact speeds 70–80 km/s [ Hornung and Kissel , ], observed temperatures of a few eV at an impact speed of about 70 km/s [ Krueger and Kissel , ], and in contrast temperatures of 10–60 eV with a weak dependence on impact speed in the range 5–100 km/s [ Ratcliff et al , ]. Subsequent observations yield 0.9–3 eV for impact speeds varying from 10 to 40 km/s [ Miyachi et al , ] and recently below 5 eV for electrons at impact speeds below 20 km/s [ Collette et al , ]. Expansion speeds have been suggested to be of the order of magnitude of the ion thermal speed and to increase with the grain's impact speed, whereas in contrast, Lee et al [] measured v E ≃15–30 km/s for masses m > 10 −17 kg impacting at 3–10 km/s, with no evidence of any variation with impact speed.…”
Section: Risetime Of Pulses In Spacecraft Potential For Nanodust Impactsmentioning
confidence: 99%
“…The top and bottom forms correspond to normal and odd events, respectively. The former form was considered to occur when the flashes during collision were directly recorded by the PM (Miyachi et al, 2008c), while the latter was considered to be a result of the superposition of flashes that occurred outside the sensitive area of the PZT element and possible secondary processes. Only those events for which an isolated single peak appeared (top of Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In addition, a dust detector designed to measure the cosmic dust around Mercury-Mercury Dust Monitor (MDM)-has been approved (Nogami et al, 2010). The MDM will be onboard the BepiColombo mission.…”
Section: Introductionmentioning
confidence: 99%